Reliability and validity of the usability scale for assistive technology for computer access: a preliminary study using video-based evaluation. - Gosselin, Livia R.; Arthanat, Sajay (Assistive Technology, 2021)
Objective: The focus of this research was to establish the interrater reliability and content validity of the Usability Scale for Assistive Technology-Computer Access (USAT-CA), an evaluation tool to facilitate selection of computer access AT devices for individuals with disabilities. Methods: AT providers used the USAT-CA to evaluate two clients with physical disabilities interacting with their computer. Initially, an expert cohort of six providers used a draft version of the USAT-CA and provided feedback. Subsequently, 13 AT providers used a revised version to evaluate the clients. The providers filled out a content validation questionnaire and recommended computer access solutions for each client. Results: Overall intraclass correlation coefficient (ICC) scores were 0.8 and 0.9 for the AT provider cohorts, respectively. In each domain, ICC scores ranged from 0.7 to 0.9. There was agreement among the providers on the tool's comprehensiveness, clarity, time needed, and utility. For Client 1, 16 out of 19 AT providers recommended speech recognition software in combination with selected direct selection interfaces. For Client 2, 14 out of 19 providers recommended ergonomic and workspace modifications. Conclusion: The USAT-CA was found to have good to excellent inter-rater reliability, good content validity, and consistency in recommendations to optimize client–computer interaction.